(untitled) (Research, Society and Development, 2022)
Introduction: Studies show an increase in pro-inflammatory cytokines in the initial phase of sleep. Nevertheless, inflammatory mediators have increased levels in situations of sleep deprivation. The increase in these levels is due to influences of the central nervous system disorder on the immune response. Objective: Review of the literature on the relationship between sleep and the immune system. Method: An active search was carried out on Scielo, EbscoHost and PubMed using the keywords “sleep and immune system”; “sleep and immunity”; “sleep-wake cycle and immunity” and “sleep and immune system”. Original articles published between 2007 and June 2021 were selected. Results: 25 articles were found, of which 15 were selected to compose the work. Discussion: Sleep deprivation causes loss of immune system integrity, with immunosuppression, decreased action of NK cells, helper T cells and phagocytic action. In addition, individuals who suffer from insomnia have an increase in pro-inflammatory cytokines, leading to an inflammatory process. The immune system produces several sleep-regulating substances, including IL-1 and TNF-a, components of innate immunity, which exert a significant influence on the sleep-wake cycle acting as somogenic molecules and modulating non-REM sleep. Conclusion: It is possible to perceive a relationship between the immune system and sleep, in which the first has sonogenic capacity and the second maintains the integrity of the immune system. Sleep deprivation triggers a decrease in the action of the immune system and exacerbation of inflammation.